(untitled) (Publicaciones en Ciencias y Tecnología, 2007)
The traveling salesman problem (TSP) is a classical combinatoric optimization problem. It consists on finding a closed path of minimum length, when connecting a collection of points on the plane. This paper describes how to use the TSP to create continuos drawline images from a picture in digital format. To do it we built TSP instances by manipulating the digital file, defining points on the plane (cities) and simplifying the pixel density in the target image in grayscale format. Then, we solve the instances by using an application which calculates the optimal tours, and so drawing the images.